Urinary Excretion of Phosphate in Normal Children - Thalassinos, N. C. (1970)
In 55 normal children on a normal diet, the phosphate and creatinine were estimated in a fasting 2-hour urine collection and in a simultaneous blood sample. In comparison with adults, a high serum phosphate and relatively decreased phosphaturia were found, both of which tended to adult values with the advent of puberty. A correlation between the serum phosphate and the urine phosphate/creatinine ratio (r = + 0·42, p <0·002) was found. The phosphate excretion index was lower in mid-childhood than in adulthood. The interpretation of any expression of phosphaturia in childhood requires its own age-specific normal range.